2007
DOI: 10.1007/s00210-007-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of capsaicin-induced relaxations in human and porcine isolated arteries

Abstract: Capsaicin, a pungent constituent from red chilli peppers, activates sensory nerve fibres via transient receptor potential vanilloid receptors type 1 (TRPV1) to release neuropeptides like calcitonin gene-related peptide (CGRP) and substance P. Capsaicin-sensitive nerves are widely distributed in human and porcine vasculature. In this study, we examined the mechanism of capsaicin-induced relaxations, with special emphasis on the role of CGRP, using various pharmacological tools. Segments of human and porcine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…Although acute exposure to capsaicin activates sensory nerve C-fibers via TRPV1 to release neuropeptides, like calcitonin gene-related peptide and substance P, prolonged exposure to capsaicin, as the protocol applied in studies of our own and others, results in desensitization of the nerve ending to further activation17,18. Noticeably, capsaicin-sensitive nerves are widely distributed in the vasculature of humans and animals19,20. Our findings from cerebral arteries are consistent with the studies of Scotland et al 7.…”
Section: Discussionsupporting
confidence: 92%
“…Although acute exposure to capsaicin activates sensory nerve C-fibers via TRPV1 to release neuropeptides, like calcitonin gene-related peptide and substance P, prolonged exposure to capsaicin, as the protocol applied in studies of our own and others, results in desensitization of the nerve ending to further activation17,18. Noticeably, capsaicin-sensitive nerves are widely distributed in the vasculature of humans and animals19,20. Our findings from cerebral arteries are consistent with the studies of Scotland et al 7.…”
Section: Discussionsupporting
confidence: 92%
“…TRPA1, like TRPV1, is expressed in neurons innervating blood vessels, and selective activation of TRPA1 can induce vasodilation via the release of CGRP (50,62). Proton-induced CGRP release has been shown to be exclusively mediated via TRPV1 activation (20,50,62). TRPV1 can release CGRP in response to ischemia-induced decrease in pH, however, the block of TRPA1 by protons could negatively modulate CGRP release.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has also been reported that activation of TRPV1 can cause vasoconstriction in mesenteric (Scotland et al, 2004), coronary (Szolcsanyi et al, 2001), and skeletal muscle arteries (Kark et al, 2008) in rodents and canines. Furthermore, capsaicin-induced relaxation of human and porcine coronary arteries is likely to be attributed to a CGRP-independent mechanism (Gupta et al, 2007). In addition, neonatal denervation of sensory nerves does not modify the NO release elicited by capsaicin, indicating that perivascular nerve fibers probably do not participate in capsaicin-induced relaxation (Rocha and Bendhack, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1, a polymodal nonselective cation channel, is expressed in sensory neurons and also present in nonneuronal tissues including blood vessels (Nilius, 2007; Pedersen et al, 2005; Vennekens et al, 2008). Apart from its role as a potent analgesic (Caterina et al, 2000), capsaicin exerts effects in the cardiovascular system (Gupta et al, 2007; Pacher et al, 2004). However, the effects of capsaicin on vascular tone and arterial pressure are a paradox.…”
Section: Introductionmentioning
confidence: 99%